Deconstructing ‘Learning Spaces’: A Narrative Inquiry on the Right to Education in Indonesia - Andaya, Raymond; Kihara-Hunt, Ai; Winanti, Kenya; Fairuza, Fathia (Human Rights in the Global South (HRGS), 2024)
This article critically examines how educational practices and spatial dynamics contribute to the (re)production of discourses surrounding the right to education. Through a narrative inquiry involving Indonesian educators working in non-state ‘learning spaces,’ it highlights both the opportunities and challenges that influence rights-oriented assessments of educational landscapes. Adopting a spatial approach to human rights analysis, the article utilises the concept of a ‘learning space’ as an analytical framework. It explores learning spaces in three key dimensions: (1) as a physical or environmental platform that demands adaptation, (2) as an agent for democratising ‘right to education’ discourses, and (3) as a flexible tool that can be managed according to the contextual needs of the educational environment. The article presents three key findings based on a spatial analysis of non-state learning spaces in Indonesia. First, while we concur with previous literature that the physical environment of learning spaces can limit pedagogical approaches and learning outcomes, it can also foster adaptable educational strategies that transform and complement traditional methodologies. Second, these spaces serve as agents of educational policy and practice, engaging with duty-bearers such as the government, civil society, parents, students, and other actors working to fulfil the right to education. Third, learning spaces are malleable tools that can be customised to suit local contexts, providing personalised learning experiences tailored to the needs of diverse student populations. While the findings of this narrative inquiry do not claim to capture all the ways learning spaces influence discourses on the right to education, the socio-spatial analysis offers a deeper understanding of how physical and social contexts shape educational rights. The article suggests directions for further research into rights-oriented educational policies and practices that take into account the flexibility and agency of non-state learning environments.